Retensi Karyawan Gen Z: Dampak Penghargaan, Pengembangan Karier, dan Kepuasan Kerja - Khujjah Ayu Asria; Juniwati Juniwati; Rizani Ramadhan; Titik Rosnani; Endah Mayasari (eCo-Buss, 2025)
The phenomenon of job hopping has become a trend among Gen Z. This generation seeks financial compensation, career development, a positive work environment, and work-life balance. In Indonesia, especially in West Kalimantan, Gen Z significantly dominates the population, so companies need effective strategies to retain their talents. This research investigates the influence of rewards and career development on employee retention, with job satisfaction as mediation. The population in this study consisted of Gen Z, who worked in cafes in West Kalimantan; the sample in this study was 211. With respondent criteria, employees who work in cafes in West Kalimantan, aged 18-27 years, with a minimum work duration of 6 months. The questionnaire was distributed online through social media platforms. The measurement and analysis tools used are SmartPLS 3 and SEM. The results showed that rewards positively and significantly affect job satisfaction and employee retention. Career development positively and significantly affects job satisfaction and employee retention. Job satisfaction has a positive and significant effect on employee retention. Job satisfaction as a mediating variable is proven to have a positive and significant impact on the relationship between rewards and employee retention, career development, and employee retention.